Penerapan Permainan Tradisional Engklek Untuk Meningkatkan Kemampuan Motorik Kasar (Keseimbangan Tubuh) Anak Usia 5-6 Tahumn Di Tk Keledang Harapan Baru - Heppy Liana; Ardilah Jumaratul Jannah; Kartika Fajriani (Manajemen Pendidikan Program Doktor, 2025)
The purpose of this study is to find out the application of traditional engklek games to improve gross motor skills (body balance) of children aged 5-6 years at Keledang Harapan Baru Kindergarten. This type of research is Classroom Action Research (PTK) with a flow of activities, namely planning, implementation, observation, and reflection in each cycle. The subjects of the study were children aged 5-6 years, 6 girls and 9 boys. The data analysis techniques used in this study are qualitative and quantitative data analysis. Qualitative data analysis is carried out through observation, interviews, and documentation. Quantitative data analysis is comparing the results obtained from pre-observation, first cycle and second cycle. The results of this study show that in the pre-cycle, an average percentage of success achievement was obtained of 32%, of which 10 children have not yet appeared and 5children have appeared only a small part with guidance. Based on the results of the research in the first cycle, the averagepercentage of success achievement was 44%, of which 9 children appeared mostly and 6 children appeared only a small part andin the second cycle it increased to 90% and met the criteria of success achievement of 80%. The conclusion of this study is that by using the traditional game media engklek can improve the gross motor skills of children aged 5-6 years in Keledang Kindergartenwith very good development criteria, because the criteria for developing very well that exceed the criteria for achieving success, the research is considered successful.